O homem do campo e os agrotóxicos: práticas e discursos no município de Novo Cabrais/RS - Bulow, Adriane Ester (2008)
This paper presents an analysis of the relationship between the rural growers of Novo Cabrais/RS with agrotoxics. Through a qualitative investigation an attempt was made to reveal the paradigms implied in the discourse of agricultural agents regarding the usage and regulation of agrotoxic products in order to provide subsidies for more effective communication strategies in future projects of rural extension. Based on growers testimony, different declarations according to different types of plantations was something striking, which makes sense taking into account the link between the company and the farmers. Tobacco growers have a close relationship with tobacco companies, from the technical assistance to the commercialization of the product, whereas the rice and soybean growers are different. They do not establish contractual relationship with companies. Therefore, they have more freedom to choose inputs and equipment and commercialize their products, thus allowing greater profitability. Despite the differences, it is noticeable that great part of the knowledge farmers have about agrotoxics , from the type and dosage to the care to be taken, is information given by professionals linked to commercial institutions. This fact shows a situation that violates the legislation , once the agronomic prescription should be issued according to visits paid to the lands by professionals not linked to the commercial sector because it represents an implicit interest in increasing sales, applying greater dosages and even more toxic than needed. Thus, the lack of objective orientation and the lack of punishment are the main factors contributing to the indiscriminate use of agrotoxics in the municipality of Novo Cabrais. This will only change with the publication of new strategies of risk communication , public policies and educational programs focused on this issue, taking into consideration the growers view on each type of plantation.